Increasing the performance of swimmers specializing in sprinting and middle distances, under different recovery modes - Gilev, G. A.; Maksimov, N. E.; Chernov, Yu. I. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to increase the performance of highly qualified swimmers at distances from 50 to 400 m in the absence, practically, of additional by-products of glycolytic metabolism. Methods and structure of the study. 28 highly qualified swimmers specializing in sprint and middle distances took part in the experiment. The difference between the subjects of the control and experimental groups was in the modes of recovery after intensive covering of distances. Athletes in the control group used a passive rest mode, and swimmers in the experimental group used swimming in an aerobic mode, without changing the method of movement. Results and conclusions. The advantage of the active recovery mode in terms of lactate concentration upon completion of intensive distance covering and its utilization during the recovery period was recorded.